Self-Reported Anxiety in Spain: A Gendered Approach One Year After the Start of COVID-19 Pandemic - Jacques-Aviñó, Constanza; López-Jiménez, Tomàs; Bennett, Matthew; Medina-Perucha, Laura; León-Gómez, Brenda Biaani; Berenguera, Anna (Frontiers in Public Health, 2022)
The COVID-19 pandemic has an impact on mental health. However, there is little evidence on how different axes of social inequity influence mental health from a gender perspective and over time. Our aim is to analyse anxiety according to gender identity and other axes of social inequities (migration status, sexual orientation, age and employment conditions) one year after the start of the COVID-19 pandemic in Spain. We conducted a cross-sectional study among adults living in Spain with an online survey from April 8 to May 28, 2021. The main variable was anxiety measured by Generalized Anxiety Disorder Scale (GAD-7). Sex-stratified multivariate ordinal logistic regression models were constructed to assess the association between axes of inequities and anxiety. Our findings (N=2,053) suggest that women have greater anxiety risk than men (35.2% vs. 28.2%, respectively). We observe in both genders that there is a clear age gradient, with anxiety decreasing as age increases; and that there is an association between worsening employment status and anxiety risk, although there is a difference between women by education level. In addition, in women not having Spanish nationality is also associated with greater anxiety risk. In men, identifying as non-heterosexual is associated with a higher risk of anxiety. The axes of inequities have different effects according to gender identity. These differences in anxiety risk by population subgroup must be taken into account in order to sensibly and equitably treat the surge in mental health disorders brought on by the COVID-19 pandemic.